一种神经细胞保护方法 (2019)
本发明公开了一种神经细胞保护方法，属于生物医学工程领域。一种神经细胞保护方法，通过等离子体处理培养的神经细胞，研究发现采用小剂量短时间处理细胞后，可以起到有效的细胞保护作用。本发明首次提出了"等离子体的细胞保护"概念，并在体外首次证明了低剂量的等离子体处理能够有效的保护HO损伤的神经细胞，不仅为神经细胞损伤修复和退行性疾病的预防和治疗研究提供了新的思路和方法，而且其价格更为低廉，操作更为简单，具有进一步开展动物在体研究和临床研究的意义，同时具有广泛的临床应用前景。 The invention discloses a nerve cells protection method, which belongs to the field of biomedical engineering. The nerve cells protection method is characterized in that the nerve cells culture by plasma, the research finds that small dosage is employed for processing cells with short time, and cells can be effectively protected. The method firstly provides a plasma cells protection conception, and firstly proves that the low dosage plasma treatment can effectively protect H2O2-damaged nerve cells, the method provides novel thinking and the method for preventing and treating nerve cell damage restoration and prevention and treatment of degenerative diseases, the cost is lower, the operation is simpler, and the method has the meaning for developing animal in-vivo study and clinic